VERNACULAR VIDEO ANALYSIS – COMMUNICATIVE CONSTRUCTION OF EVIDENCE IN POLICE WORK - TUMA, RENÉ (Society Register, 2019)
Abstract The use of video recordings for the production of knowledge has spread all over society. This paper presents an empirical study of the processes of interpretation of audio-visual recordings. It draws on an example in the context of police work and on the other side investigation of recordings of police violence. With a theoretical background in communicative constructivism special attention is given to situated bodily forms of “making things visible” performed by the participants. Interpretation is not understood as an pure cognitive but rather an communicative process. I elaborate on that by presenting results of (reflexive) videography of practices of video-interpretation. However, the specifics of the work are not only brought upon situatively, but are embedded in an institutional and organizational context. This paper draws on the concept of work arcs, that allow to highlight the trans-situative linkage.